ELIGIBILITY OF A CONTRIBUTIONS IN KIND AS A SUBJECT OF AN OBLIGATION TO INVEST IN A LIMITED LIABILITY COMPANY - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
A contribution is an economic value that, whether in cash or in kind form, is always expressed in money, which the founder, member or person accessing the company subscribes to, pays and, or enters into the company and from which the share capital is formed. According to the Serbian Law on Companies, the contributions in company may be pecuniary or in kind and are expressed in dinars. However, the Serbian Companies Act does not contain a definition of contributions in kind, but only a provision that contributions in kind may be in matters and rights, unless otherwise provided by that law for certain forms of companies. In comparative law, a negative definition of contributions in kind is generally encountered. Contributions in kind are contributions where the contribution is not made in cash. Such a negative definition of contributions in kind leaves open the question of what concrete, but not money, can be considered a permissible contribution in company. The provision of the Serbian Law on Companies that contributions in a limited liability company can be exclusively in matters and rights is also not sufficiently clear and elaborated, so the object of the analysis of this paper will be to clarify the general conditions that contributions in kind generally, as well as certain emerging forms of contributions in kind (especially rights) should be fulfilled in order to be eligible to be subject to an obligation to enter contributions.